Small-scale movements and site fidelity of two sympatric sea turtle species at a remote atoll - Cheryl L. Sanchez; Nancy Bunbury; Jeanne A. Mortimer; Luke A’Bear; Jennifer Appoo; Michael Betts; Rainer von Brandis; Lorraine Cook; Janske van de Crommenacker; Jock C. Currie; Naomi Doak; Frauke Fleischer-Dogley; et al. (Marine Biology, 2024)
Understanding natural movement patterns and ecological roles of marine megafauna is a research priority best studied in areas with minimal human impact. The spatial distribution patterns specifically for immature turtles at foraging grounds have been highlighted as a research gap for effective management and conservation strategies for sea turtle populations. Capture–mark–recapture (CMR) records ( n = 2287) of 1672 immature green ( Chelonia mydas ) ( n = 1158) and hawksbill turtles ( Eretmochelys imbricata ) ( n = 514) from a long-term (1981–2021) in-water CMR program at Aldabra Atoll, Seychelles, were analyzed for 10 sites (0.35–25 km apart). Site fidelity was not correlated with either season or turtle size. Green turtles had lower site fidelity than hawksbill turtles. Green turtles showed avoidance (i.e., opposite of fidelity) of three sites, while hawksbill turtles displayed high fidelity to two sites. Sites displaying non-random behavior (avoidance and/or fidelity) did not share the same benthic habitat types. Results indicate that fidelity can be detected at a fine scale with CMR, but that further exploration into the habitat characteristics of the sites and the ecological roles of both species at the atoll is needed.